The role of (pro)renin receptor and its soluble form in cardiovascular diseases - Wang, Boyang; Jie, Haipeng; Wang, Shuangxi; Dong, Bo; Zou, Yunzeng (Frontiers in Cardiovascular Medicine, 2023)
The renin-angiotensin system (RAS) is a major classic therapeutic target for cardiovascular diseases. In addition to the circulating RAS, local tissue RAS has been identified in various tissues and plays roles in tissue inflammation and tissue fibrosis. (Pro)renin receptor (PRR) was identified as a new member of RAS in 2002. Studies have demonstrated the effects of PRR and its soluble form in local tissue RAS. Moreover, as an important part of vacuolar H+-ATPase, it also contributes to normal lysosome function and cell survival. Evidently, PRR participates in the pathogenesis of cardiovascular diseases and may be a potential therapeutic target of cardiovascular diseases. This review focuses on the effects of PRR and its soluble form on the physiological state, hypertension, myocardial ischemia reperfusion injury, heart failure, metabolic cardiomyopathy, and atherosclerosis. We aimed to investigate the possibilities and challenges of PRR and its soluble form as a new therapeutic target in cardiovascular diseases.